Controlling Soil Loss through Proper Cover (Specially in the Hills) - Agarwal, S. C.; Rege, N. D. (Indian Forester, 1960)
Factors affecting soil erosion like state of soil, its fertility, degree of slope, intensity of rainfall etc., are essential for consideration while planning soil conservation measures. But no amount of soil Conservation measures are fully effective without planning for adequate vegetative cover. The vegetative cover reduces run off and checks soil loss by interception, addition of organic matter to the soil thus improving the structure of the soil affecting porosity and infiltration -and even affording mechanical obstruction to the moving soil particles. The article deals with some trends seen in the studies carried out for determining the effectiveness of different covers in controlling run-off and soil loss and their effectiveness in changing porosity, infiltration etc. through addition of organic matter to the soil.